Chamfered-bowl piston for ultra-low particulate combustion with diesel and soybean biodiesel in a single-cylinder compression-ignition engine. (August 2015) - Kim, Junghwan; Oh, Seungmook; Lee, Yonggyu; Lee, Sunyoup; Kim, Duksang; Lee, Youngjae; Huh, Kang Yul
Piston bowl geometries are critical to the combustion and emission characteristics of diesel engines. The present study investigated chamfered-bowl designs and biodiesel blending under a low-temperature combustion regime in order to achieve ultra-low particulate combustion (ULPC). The target soot level for ULPC was set at a filter smoke number value of 0.1 and engine experiments were conducted at the medium load condition. The injection visualization experiment provided the start of injection difference between the diesel and biodiesel fuels, while a three-dimensional computational simulation was conducted to examine the spray and combustion phenomena inside the engine cylinder. The experimental engine was a 1 l single-cylinder diesel engine equipped with a common-rail direct-injection system. The engine was operated at a speed of 1400 rev/min and the intake pressure was set at 200 kPa for a 50 per cent load condition. Two chamfered-bowl pistons were prepared for comparison with the conventional re-entrant bowl piston, and the experimental results showed that the chamfered-bowl pistons achieved significant soot reduction. In addition, computational analysis using a KIVA model showed that the chamfered bowls achieved wider fuel distribution and enhanced combustion. Biodiesel blending further reduced soot emission, and an increase in nitric oxides with biodiesel blends was also observed.